Bizancjum a świat łaciński w pismach Zygmunta Krasińskiego = Byzantium and the Latin world in the writings of Zygmunt Krasiński - Krysowski, Olaf (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Zygmunt Krasiński suggested in his philosophical and political writings from 1841-1858 that thehistory of the Slavs, as well as the whole mankind, is ruled by the law of the battle between two opposing moral elements: good and evil. Such an interpretation of history had far-reaching ideologicalimpact on the poet`s works. It contributed to the concept of Russia and Poland as two group spiritsthat are hostile towards each other: dark and bright, demonic and angelic. In this way, the poet translated the idea of battle between opposing ethical values, which is characteristic for some religious beliefs, directly into historical reality.
Keywords: Krasiński, Zygmunt (1812-1859); literatura polska - historia - 19 w.